Erweiterte Systemmodellierung - Integration impliziter Wissenselemente in die Erstellung technischer Systemmodelle - Wilking, Fabian; Walter, Leonie; Schleich, Benjamin; Wartzack, Sandro (Beiträge zum 31. DfX Symposium, 2020)
The increasing complexity of technical consumer products has led to the integration of Model-Based Systems Engineering (MBSE) approaches into sectors that are not viewed as classic users of Systems Engineering. The approach helps grasping the complexity and keeping costs at a low level. However, many companies struggle with the implementation of the approach into their processes. A regularly mentioned reason for this is a missing visibility of a clear benefit. Especially smaller enterprises are facing these problems within the value chain. This paper presents an approach to contribute towards the enhancement of MBSE accessibility. It shows different strategies for the integration of tacit knowledge into system models and discusses their feasibility and contribution towards this enhancement.
Keywords: Systems Engineering; Model-Based Systems Engineering; System Model; Knowledge Management; Tacit Knowledge